Archaic Societies : Diversity and Complexity across the Midcontinent - Ahler, Steven R.; Benn, David W.; Buikstra, Jane E.; Butler, Brian M.; Cantin, Mark; Demel, Scott J.; Ellis, Christopher; Emerson, Thomas E.; Emerson, Thomas E.; Farnsworth, Kenneth B.; Fishel, Richard L.; Fortier, Andrew C; et al. (SUNY Press, 2012)
Sweeping and detailed, this long-awaited volume is an indispensable guide to the Archaic period across the midcontinent. Archaeologists throughout the region share the latest excavation results and analytical perspectives to reveal and reinterpret the worlds of those Native peoples who lived there for some 9,000 years (up to about 3,000 years ago). Of particular concern is the establishment of relative and absolute chronologies for the Archaic period, the relationships between the artifacts left behind and the peoples who made and used them, and the changing interactions between cultures, climate, and landscape. Archaeologists offer useful, up-to-date overviews of Archaic societies, assessment of stratigraphic sequences, and detailed discussions of finds and interpretations from the Mississippi and Ohio river regions and the Great Lakes. Comprehensive and accessible, this landmark book is a must for anyone wanting to understand a crucial but little-understood period in North America's prehistory.